2019
DOI: 10.1038/s41467-019-08824-8
|View full text |Cite|
|
Sign up to set email alerts
|

Room temperature CO2 reduction to solid carbon species on liquid metals featuring atomically thin ceria interfaces

Abstract: Negative carbon emission technologies are critical for ensuring a future stable climate. However, the gaseous state of CO 2 does render the indefinite storage of this greenhouse gas challenging. Herein, we created a liquid metal electrocatalyst that contains metallic elemental cerium nanoparticles, which facilitates the electrochemical reduction of CO 2 to layered solid carbonaceous species, at a low onset potential of −310 mV vs CO 2 /C. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
254
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(261 citation statements)
references
References 28 publications
5
254
2
Order By: Relevance
“…It can also be seen that, as the weight percentage of graphene increases, the intensities of two main PDMS peaks at 2905 and 2960 cm −1 (symmetric and antisymmetric CH 3 stretching vibrations) decrease accordingly. Furthermore, despite the low concentration, the Raman signals of graphene at 1379 (D band) and 1601 cm −1 (G band) can be noticed . Additionally, an evident enhancement of these graphene Raman peaks can be observed as the graphene loading increases from 0.6 to 3.0 wt%.…”
Section: Resultsmentioning
confidence: 92%
“…It can also be seen that, as the weight percentage of graphene increases, the intensities of two main PDMS peaks at 2905 and 2960 cm −1 (symmetric and antisymmetric CH 3 stretching vibrations) decrease accordingly. Furthermore, despite the low concentration, the Raman signals of graphene at 1379 (D band) and 1601 cm −1 (G band) can be noticed . Additionally, an evident enhancement of these graphene Raman peaks can be observed as the graphene loading increases from 0.6 to 3.0 wt%.…”
Section: Resultsmentioning
confidence: 92%
“…In our work, the selected method is the best preparation condition among various expansion conditions, determined after tests with different types of solvents and reaction times in the solvents. Further details of the experimental method are described in our previous work [16] and in the experimental section. Figure 1b shows digital images of the KC 8 (before) and the df -GNS (after) in the pyridine solution before and after the expansion process.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Lee et al suggested a nanohole-structured architecture synthesized from gelatin-functionalized GO via microwave irradiation, resulting in a high rate performance with stable capacity retention [15]. Furthermore, the Daeeke, Kalantar-zadeh, and Yeo groups have suggested new methods for fabricating layered solid carbonaceous materials collected from CO 2 conversion and their application to capacitors [16], as well as peeling off bulk 3D piezoelectric crystals (WS 2 and MoS 2 ) to 2D nanosheets by using high frequency acoustic waves [17]. However, oxygen functional groups ascribed to strong oxidation chemicals (H 2 O 2 , HNO 3 , and KMnO 4 ) and imperfect crystal recovery rates have mainly led to limited performance improvements in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…However, whereas the authors obtained some graphene‐like material, most of the product resulted in amorphous carbon. More recently, it was shown that CO 2 can be electrochemically reduced to carbonaceous species at room temperature employing ceria catalysts . In this regard, herein we present a one‐step synthesis of graphene using CO 2 gas, as carbon feedstock, and Cu–Pd substrates, employing an atmospheric pressure chemical vapour deposition (APCVD) reactor.…”
Section: Introductionmentioning
confidence: 98%